Exploring The Needs Of Junior High School Teachers And Students In The Development Of Digital Modules For Writing Non-Literary Texts Based On Local Culture - Denny Indria Ferawati; Ari Kusmiatun (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Writing instruction at the junior high school level requires the availability of modules that are aligned with the curriculum, relevant to the cultural context, and in line with developments in digital technology. Some of the teaching materials used in writing instruction are still conventional and do not integrate local cultural values or optimal digital features. This situation indicates a gap between the needs in the field and the availability of interactive and contextual teaching materials. This study aims to explore the needs of teachers and students in developing digital modules for writing non-literary texts based on local culture as a basis for developing innovative writing modules in junior high schools. The method used is a qualitative approach with data collection techniques through interviews, questionnaires, and documentation studies analyzed using triangulation. The participants in this study consisted of Indonesian language teachers and junior high school students. The results of the study indicate that teachers and students need writing modules that are interactive, accessible online, communicative, and equipped with step-by-step guides. Another important finding is the need for local cultural content that can foster creativity and a sense of belonging to regional identity. The novelty of this research lies in the development of digital modules that integrate local cultural content to foster students' creativity in writing and their appreciation of local cultural values. This finding emphasizes the importance of developing modules that are tailored to the needs of users. This research contributes to the study of contextual digital module design and writing learning innovation in the era of digital literacy.